Developing Professional Training of Physical Culture Teachers (Eurasian Journal of Learning and Academic Teaching, 2023)
This article discusses the formation of a professional readiness for a physical culture teacher. The author highlights the importance of a comprehensive approach to the formation of professional competencies, including pedagogical, psychological, and methodological aspects. The article also emphasizes the significance of practical training and continuous professional development for physical education teachers. The author argues that the development of professional skills is essential for ensuring the quality of physical education and creating a positive learning environment for students. Overall, the article provides insights into the requirements and challenges of the profession of a physical culture teacher and offers recommendations for effective professional development.